PERAN KEPALA SEKOLAH DALAM IMPLEMENTASI KURIKULUM 2013 DI SMAN 2 BENGKULU SELATAN - Muhadzdzibah Muhadzdzibah; Manap Somantri; Puspa Djuwita (UNIVERSITAS BENGKULU, 2017)
The problems in the research are how are the roles of the Principal in Implementing of The Curriculum 2013, and the prospect In other Schools. Based on the data Analysis, It can be Summarized that the Preparation of the Curriculum 2013 Implementation of The Principal plays a very Important role as The principal’s main jobs, functions and roles as the school manager, by setting the plans of action programs, the personal organizing deciding the organizing staffs and calculating the budget; actuating the learning process, giving the guidance, coordinating all staffs , controling all programs, monitoring the implementation of the programs and presenting the report, making an innovation in doing the job and motivating the staffs, visiting the class, observing, and guiding, analysing all the constraints and deciding the next actions.